Integration of ion exchange resin materials for a downstream‐processing approach of an imine reductase‐catalyzed reaction. (16th June 2020) - Meyer, Lars‐Erik; Brundiek, Henrike; von Langermann, Jan
Abstract: In this study, an ion exchange resin‐based downstream‐processing concept for imine reductase (IRED)‐catalyzed reactions was investigated. As a model reaction, 2‐methylpyrroline was converted to its corresponding product ( S )‐2‐methylpyrrolidine with >99% of conversion by the ( S )‐selective IRED from Paenibacillus elgii B69. Under optimized reaction conditions full conversion was achieved using a substrate concentration of 150 and 500 mmol/L of d ‐glucose. Seven commercially available cation‐ and anion‐exchange resins were studied with respect to their ability to recover the product from the reaction solution. Without any pretreatment, cation‐exchange resins Amberlite IR‐120(H), IRN‐150, Dowex Monosphere 650C, and Dowex Marathon MSC showed high recovery capacities (up to >90%). A 150‐ml preparative scale reaction was performed yielding ~1 g hydrochloride salt product with >99% purity. Any further purification steps, for example, by column chromatography or recrystallization, were not required. Abstract :